Good practices on ESG reporting in the context of the European Green Deal - Alexandra Dănilă; Maria-Gabriela Horga; Oana Oprișan; Tănase Stamule (Amfiteatru Economic Journal, 2022)
The European Green Deal proposes a series of measures to the EU Member States in order to adopt policies on how to use and produce green energy, support new clean technologies, and reduce noise, air and water pollution. The target referring to reducing emissions by at least 50% by 2030 has already strongly impacted Europe on social, economic and environmental levels, as well as the business sector. This study begins by highlighting the importance of complying with social, environmental, and governance reporting of large companies and the banking sector alike in the context of adopting the European Green Deal. Furthermore, we continue by showcasing how the new disclosure requirements and recommendations have been adapted and translated into non-financial ESG reporting (environmental, social, and governance impact of economic activity). Finally, we present a series of best practices in this area. As the present study has revealed the need to improve ESG reporting, good-practice recommendations were identified and formulated.
Keywords: G20; G30; G38; F64; 330; best practices; environmental factors; ESG non-financial reporting; governance; social factors